Factors associated with violence in bipolar disorder versus major depressive disorder: insights from a retrospective cross-sectional study of 141 aged patients with mood disorders - Ye, Junrong; Zhou, Tingwei; Lei, Lingli; Mo, Lili; Chen, Jiao; Wang, Wen; Wei, Yanheng; Lu, Xueling; Yuan, Lexin; Wu, Shengwei; Li, Zezhi; Zheng, Dandan; et al. (Frontiers in Psychiatry, 2026)
ObjectiveThis study aims to explore the risk factors and protective factors associated with violence in patients with mood disorders and to identify the differences in these risk factors between clinical subtypes: bipolar disorder (BD) and major depressive disorder (MDD).MethodsA retrospective cross-sectional investigation was conducted from February 2021 to March 2024. Participants were consecutively sampled from the geriatric psychiatric ward of a tertiary psychiatric hospital. The general information questionnaire, Brøset Violence Checklist (BVC), Geriatric Depression Scale (GDS), and Functional Activity Questionnaire (FAQ) were used to evaluate the risk of violence, depressive syndromes, and activities of daily living of the participants.ResultsAmong the 141 elderly patients with mood disorders, 40 (28.4%) were diagnosed with bipolar disorder and 101 (71.6%) with major depressive disorder. The sample included 34.8% males and 65.2% females, with an average age of 67.42 ± 6.91 years. Regarding educational attainment, 12.1% had completed a bachelor’s degree or higher, 22.7% had completed senior school or an associate degree, and the majority (65.2%) had received education at the junior high school level or below. Unhealthy lifestyles, such as smoking and alcohol use, were relatively uncommon, with 7.1% smoking and 5% consuming alcohol. Univariate analysis of elderly patients with mood disorders revealed that gender, smoking status, first admission, type of admission, length of hospitalization, and restraint condition were significantly related to the risk of violence (P < 0.05). Additionally, the GDS and FAQ scores showed statistically significant differences (P < 0.05). Multiple linear regression analysis indicated that abnormal GDS scores (β = -0.424, P < 0.001), restraint condition (Yes) (β = 0.181, P < 0.05), and length of hospitalization (>14 days) (β = 0.145, P < 0.05) were significant factors influencing the risk of violence in hospitalized elderly patients with mood disorders. Specifically, for patients with MDD, abnormal GDS scores (β = -0.207, P < 0.05) and restraint condition (Yes) (β = 0.437, P < 0.001) were significant factors. For patients with BD, the length of hospitalization (>14 days) (β = 0.260, P < 0.05) was a significant factor influencing the risk of violence.ConclusionPatients with mood disorders have a potential risk of violence, and the clinical factors influencing this risk differ between clinical subtypes. Therefore, given these distinct risk profiles across subtypes, precise risk assessment and early intervention are necessary to mitigate the risk of violence in these patients.